Factors Related to The Incident of Preeclampsia in Pregnant Women in Banjar District - Firdha Yuserina; Winardi Budiwinata; Fauzie Rahman; Husnul Fatimah; Wetha Exavarani Susanto; Zuhrufa Wanna Yolanda; Melati Noormaulidya Putri; Hamdanah Hamdanah; Nina Ulfatin Khaira; Nor Annisa; Chairul Ramadhan (Lambung Mangkurat, 2023)
Preeclampsia is high blood pressure that often occurs at 20 weeks of gestation until the end of the first week after pregnancy, which is the second highest factor after bleeding which is the cause of maternal death. This study analyzes variables related to factors related to the incidence of preeclampsia in pregnant women in Banjar Regency, South Kalimantan Province. This study used a cross-sectional research design and used the Fisher exact test with a CI of 0.05 (95%). The sampling technique uses random sampling. The results obtained were that 12 pregnant women who experienced preeclampsia out of 50 respondents. In addition, the results of the study showed that there was no relationship between age (1,000), parity (0.490), and anxiety (1,000) on the incidence of preeclampsia in pregnant women in Banjar Regency. Many factors that may influence whether a pregnant woman will experience preeclampsia or not, this is why all the factors studied are not related to the incidence of preeclampsia.